Genomic Sequencing and Analysis of a Novel Human Cowpox Virus With Mosaic Sequences From North America and Old World Orthopoxvirus - Diaz-Cánova, Diana; Moens, Ugo L.; Brinkmann, Annika; Nitsche, Andreas; Okeke, Malachy Ifeanyi (Frontiers in Microbiology, 2022)
Orthopoxviruses (OPXV) not only infect their natural hosts but can also cause disease in humans. Previously, we partially characterized an orthopoxvirus isolated from an 18-year-old male living in Northern Norway. Electron microscopy studies and partial genome sequencing characterized this virus as an atypical cowpox virus, which we named CPXV-No-H2. In this study, we determined the complete genome sequence of CPXV-No-H2 using Illumina and Nanopore sequencing. Our results showed that the whole CPXV-No-H2 genome is 220,276 base-pairs (bp) long with inverted terminal repeats regions of approximately 7 kbp, containing 217 predicted genes. Seventeen predicted CPXV-No-H2 proteins were most similar to OPXV proteins from the Old World, including Ectromelia virus and Vaccinia virus, and the North America, Alaskapox virus. CPXV-No-H2 has a mosaic genome with genes most similar to other OPXV genes and seven potential recombination events were identified. Phylogenetic analysis showed that CPXV-No-H2 formed a separate clade with the German CPXV isolates CPXV_GerMygEK938_17 and CPXV_Ger2010_MKY, sharing 96.4% and 96.3% nucleotide identity, respectively and this clade clustered closely with the ECTV-OPXV Abatino clade. CPXV-No-H2 is a mosaic virus that may have arisen out of several recombination events between OPXV and its phylogenetic clustering suggests that ECTV-Abatino-like cowpox viruses form a distinct, new clade of cowpox viruses.